Circum Mare. Themes in ancient warfare - Armstrong, Jeremy. (Mnemosyne, Supplements, 2016)
Circum Mare: Themes in Ancient Warfare presents a thematic approach to current directions in ancient military studies with case studies on topics including the economics of warfare, military cohesion, military authority, irregular warfare, and sieges. Bringing together research on cultures from across the Mediterranean world, ranging from Pharaonic Egypt to Late Antique Europe and from Punic Spain to Persian Anatolia, the collection demonstrates both the breadth of the current field and a surprising number of synergies.